2018
DOI: 10.1007/s00259-017-3925-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of receptor radionuclide therapy with 177Lu-DOTATATE in patients with GEP-NEN and a high Ki-67 proliferation index

Abstract: Lu-PRRT showed antitumour activity in SRI+ GEP-NENs of intermediate and high-grade. DCR and PFS were significantly better in patients with a Ki-67 index of ≤35% than in those with a Ki-67 index of >35%. On the basis of these results, PRRT should be considered as a therapeutic option in patients with high-grade SRI+ GEP-NENs, in particular those with a Ki-67 proliferation index of ≤35%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 27 publications
4
49
0
2
Order By: Relevance
“…Six of the 13 studies included in Tables 4-6 do not include outcomes of the G3 patients, and only 4 commented on the degree of differentiation. Of the 7 (7/13) studies (29)(30)(31)(32)(33)(34)(35) that directly measured the outcome of the G3 patients, there were a total of 151 patients in whom imaging studies could be tracked over time after receiving PRRT. Of these 151 patients, 99 (66%) demonstrated either stable disease, partial response, or complete response.…”
Section: Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the 13 studies included in Tables 4-6 do not include outcomes of the G3 patients, and only 4 commented on the degree of differentiation. Of the 7 (7/13) studies (29)(30)(31)(32)(33)(34)(35) that directly measured the outcome of the G3 patients, there were a total of 151 patients in whom imaging studies could be tracked over time after receiving PRRT. Of these 151 patients, 99 (66%) demonstrated either stable disease, partial response, or complete response.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Considering the heterogeneity of the data, it is difficult to identify any specific characteristics that may predict response to PRRT in G3 NENs, given that the tumors were located in many different primary sites and the PRRT included a mix of 177 Lu and 29reported significantly better outcomes in patients with a Ki-67 of no more than 55%, similar to the NORDIC study. The data from the study by Nicolini et al (30) include 5 patients with a Ki-67 of between 15% and 20% and 8 patients with a Ki-67 of 20%, but the data do not track disease response from these patients apart from the other 20 patients with a Ki-67 of more than 20%. This factor may explain why the patients reported in their study had an overall better response than in some of the others in Tables 4-6.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Ein höherer Ki-67-Index war mit einem kürzeren progressionsfreien Überleben verbunden [48]. Während diese Daten vielversprechend für die Anwendung von 177 Lu-DOTA-TATE bei G3-Tumoren sind, zeigte eine andere retrospektive Auswertung eine deutlich niedrigere Ansprechrate [49]. In dieser post-hoc-Analyse von Daten einer Subgruppe von 33 Patienten, die im Rahmen einer prospektiven Phase II-Studie behandelt worden waren, betrug die Ansprechrate nur 6 %.…”
Section: Studieunclassified
“…In dieser post-hoc-Analyse von Daten einer Subgruppe von 33 Patienten, die im Rahmen einer prospektiven Phase II-Studie behandelt worden waren, betrug die Ansprechrate nur 6 %. Das progressionsfreie Überleben war mit 23 Monaten aber wiederum vielversprechend [49]. Es muss auch bedacht werden, dass nur etwa 40 -70 % der G3-neuroendokrinen Tumore eine Überexpression von Somatostatinrezeptoren zeigen und für eine Therapie mit 177 Lu-DOTA-TATE prinzipiell geeignet sind [21].…”
Section: Studieunclassified
“…9 Recently, 177 Lu-PSMA and 177 Lu-DOTA-TATE have been used in prostate cancer and neuroendocrine tumors, respectively, and achieved satisfactory results. [10][11][12][13] DTPA can be easily and efficiently labeled with 177 Lu with high radiochemical purity and stability. 14 Previous studies have shown that DTPA-DG may be used as a radiopharmaceutical agent for tumors.…”
Section: Introductionmentioning
confidence: 99%